Long-term outcomes of gonadotropin-releasing hormone agonist treatment in girls with central precocious puberty - Jung Hwangbo; Eungu Kang; Hyo-Kyoung Nam; Young-Jun Rhie; Kee-Hyoung Lee (Annals of Pediatric Endocrinology & Metabolism)
Purpose This study aimed to examine the effects of gonadotropin-releasing hormone agonist (GnRHa) treatment on final height outcomes in girls with idiopathic central precocious puberty (CPP) from the start of treatment to their postmenarche visit. Methods We conducted a retrospective analysis of 200 girls with idiopathic CPP who received GnRHa therapy, focusing on auxological and clinical outcomes at treatment initiation, treatment completion, and the last, postmenarche visit. Results The mean chronological age (CA) at GnRHa treatment initiation was 8.24±0.73 years. The mean duration of GnRHa treatment was 3.12±0.81 years. The average age at menarche was 12.73±0.56 years, occurring a mean of 17.15±5.52 months after completing GnRHa therapy. The predicted adult height (PAH) standard deviation score (SDS) after menarche (0.48±0.99) was significantly greater than before treatment (-1.33±1.46) (P<0.001). Factors including greater bone age advancement (P<0.001), lower height SDS for CA at treatment initiation (P<0.001), and higher midparental height SDS (P=0.001) were positively associated with an increase in PAH SDS at the last visit. However, near-final height and the increase in PAH SDS at the last visit were not significantly different between patients who received early treatment (<8 years) and those who received later treatment (8–9 years). Conclusions GnRHa treatment improved the final height outcomes in all girls with CPP, including those treated between 8 and 9 years of age.